Facial neurology: paroxysmal neuralgia (a contribution by Professor Karlov) - O. O. Yanushevich; S. A. Rabinovich (Эпилепсия и пароксизмальные состояния)
This report has been dedicated to study facial neurology, which were profoundly impacted by Professor V.A. Karlov. Dento-neurology as a separate medical field assessing diagnostics and treatment of face and neck pain syndrome, therapy of cerebral-cranial nerves and defuncted maxillotemporal joint. Importance of visualization techniques used upon therapy of trigeminal neuralgy was emphasized.